Geometric Analysis of Complex Endovascular Treatment of a Successfully Completed Residual Post-Type A Aortic Dissection - Finotello, Alice; Pane, Bianca; Di Bartolo, Mauro; Del Pizzo, Rachele; Mambrini, Simone; Pratesi, Giovanni; Spinella, Giovanni (AORTA, 2022)
We describe a case of complex multistep endovascular treatment of a post-Type A thoracoabdominal dissected aneurysm. Volume analysis documents true and false lumen improvements during follow-up. Centerline tortuosity of the aorta and of the iliac arteries straightens after endovascular treatment completion. In addition, analysis of stent-graft remodeling reveals the stent-graft tendency to spring back to its original status together with a caudal migration of the fenestrated body.
Keywords: residual Type A dissection; TEVAR; geometric analysis